Indefinite pronouns in Assamese - Bhattacharyya, Pushpa Renu (Nepalese Linguistics, 2018)
The study describes the indefinite pronouns in Assamese with its complexity and unique features and put emphasis on the morphological, semantic and syntactic properties. The term pronoun is used in the sense of the nominal expression and the substitution in the nominal slot only.